Evaluation of the Knowledge and Behaviors of Gazi University Medical Faculty Students on Rational Use of Medicines - Hızal, Özgecan Gül; Özçelik, Mehmet Alperen; İlhan, Mustafa Necmi (Turkey Health Literacy Journal, 2021)
Objective: The aim of this study was to evaluate the knowledge and behavior of Gazi University Faculty of Medicine students regarding rational use of medicines before graduation.Method: The population of the research, which was planned as a descriptive study, consists of 1st, 2nd, 3rd and 4th grade students of Gazi University Faculty of Medicine. A total of 145 students participated in the study, and an online questionnaire consisting of 33 questions on sociodemographic characteristics and rational drug use behaviors was conducted. SPSS-23 package program was used for statistical analysis of the data. In the descriptive statistics section, categorical variables were presented as numbers and percentages, and continuous variables were presented as mean ± standard deviation and median. Chi-square test was used in the comparison analyzes of categorical variables, and the statistical significance level was accepted as p
Keywords: Rational Use of Medicines, Faculty of Medicine, Medical Education, Pre-Graduation Education.